Peran Indeks Pembangunan Manusia dan Kesejahteraan Terhadap Kemiskinan dan Laju Pertumbuhan Penduduk Di Indonesia - Anis Salsabila; Zahra Ramadhani; Goklas Purba; Muhammad Alif Zuanda4; Asnidar Asnidar; Ahmad Ridha (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
In order to better understand how to manage Indonesia's population and reduce poverty, this study will use welfare and the human development index (HDI) as its metrics. This research made use of secondary data that was given by the Central Bureau of Statistics in Indonesia. Analyzing the relationship between the dependent variables (poverty and population growth rate) and the independent ones (welfare and the human development index) requires the use of expert analysis. The results show that in order to control the pace of population increase in Indonesia and reduce poverty, wealth and the human development index are very important. These results have significant ramifications for Indonesian development strategy in order to enhance human development quality and efficiently regulate population density